International dimensions of organizational behavior - Adler, Nancy J (Thomson/South-Western, 2008)
pt. 1. The impact of culture on organizations. ch. 1. Culture and management -- ch. 2. How cultural differences affect organizations -- ch. 3. Communicating across cultures -- pt. 2. Leveraging cultural diversity. ch. 4. Creating cultural synergy -- ch. 5. Managing multicultural teams -- ch. 6. Leading globally -- ch. 7. Motivating people from around the world: inspiring people to contribute -- ch. 8. Multinational decision making -- ch. 9. Negotiating globally -- pt. 3. Managing global managers. ch. 10. Managing cross-cultural transitions: moving abroad and coming back home -- ch. 11. A portable life: the expatriate spouse -- ch. 12. Global careers: succeeding in the 21st century; Includes bibliographical references and index; Aimed at readers who wish to understand the implications of world cultures in the workplace, this book takes the point of view that culture does impact the organization, and that it has its most significant impact at the micro level - at the level of people communicating, working, and negotiating with other people